SHAVKAT RAHMON'S LIFE AND WORK - Ismoilova Mushtariybegim (Researchparks Publishing, 2023)
A unique representative of 20th century Uzbek poetry, the nationalist poet Shavkat Rahmon was born on September 12, 1950 in the city of Osh. The poet's father, Rahmonberdi, originally came from the village of Sarai in the Shahrikhan district, and by the will of fate he came to the city of Osh. The poet's mother was also originally from Shahrikhan district. Their family was engaged in trade, from early morning until late autumn, they supplied the herdsmen in the Sarmogul pastures at the foot of the Pamir Mountains with the necessary food and household items. would provide. All work in the house was the responsibility of the imaginative, but diligent, hard-working eldest child, Shavkat Rahman.